2001
DOI: 10.1073/pnas.141224198
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic forces generated by myosin II and cytoplasmic dynein regulate microtubule turnover, movement, and organization in interphase cells

Abstract: Photoactivation of caged fluorescent tubulin was used mark the microtubule (MT) lattice and monitor MT behavior in interphase cells. A broadening of the photoactivated region occurred as MTs moved bidirectionally. MT movement was not inhibited when MT assembly was suppressed with nocodazole or Taxol; MT movement was suppressed by inhibition of myosin light chain kinase with ML7 or by a peptide inhibitor. Conversely, MT movement was increased after inhibition of cytoplasmic dynein with the antibody 70.1. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
3
28
1
Order By: Relevance
“…S4). These results are consistent with recent live-cell imaging analyses demonstrating a significant decrease in the turnover (extension and shrinkage) of cortical microtubules in fibroblasts and epithelial cells after pharmacological inhibition of either myosin II itself (EvenRam et al, 2007) or its activator, myosin light chain kinase (Yvon et al, 2001). Taken together, these data suggest that loss of cortical actin filaments following myosin II inhibition dramatically affects the spatial distribution of microtubules, leading to their outgrowth to the submembranous compartment and initiation of peripheral protrusions.…”
Section: Discussionsupporting
confidence: 92%
“…S4). These results are consistent with recent live-cell imaging analyses demonstrating a significant decrease in the turnover (extension and shrinkage) of cortical microtubules in fibroblasts and epithelial cells after pharmacological inhibition of either myosin II itself (EvenRam et al, 2007) or its activator, myosin light chain kinase (Yvon et al, 2001). Taken together, these data suggest that loss of cortical actin filaments following myosin II inhibition dramatically affects the spatial distribution of microtubules, leading to their outgrowth to the submembranous compartment and initiation of peripheral protrusions.…”
Section: Discussionsupporting
confidence: 92%
“…Observations of the microtubule array suggested that the treatments prevented the full extension of microtubules into the cell periphery. There is a well-known antagonism between microtubule-and actinbased cytoskeletal components, which may affect formation and turnover of focal contacts at the cell edge (88,89). If focal contacts were stabilized by microtubule withdrawal, this could explain the increased prevalence of filopodia in treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution was determined, by one-way analysis of variance, to be random, with 31% in the front, 29% on the side, 22% in the back, and 18% in the center, demonstrating that cytoplasmic dynein/dynactin does indeed play a role in MTOC reorientation in CHO cells at the wound edge (Table 2). Cells injected with 70.1 antibodies were characterized by less-well-organized microtubule arrays (Yvon et al, 2001) and, although lamellae did form at the leading edge, locomotion was somewhat reduced compared with control cells.…”
Section: Centrosome Reorientation In Fibroblasts Requires Cytoplasmicmentioning
confidence: 94%
“…Preparation of labeled tubulins, photoactivation, and image collection were performed exactly as described previously (Yvon et al, 2001).…”
Section: Image Acquisitionmentioning
confidence: 99%